Diversifikasi Produk Gula Semut dan Kemasan Pada UKM “Mekri” Di Desa Koreng Kecamatan Tareran Kabupaten Minahasa Selatan Propinsi Sulawesi Utara - Mikke R Marentek; Nancy H.J Mandey (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
UKM MEKRI is a craftsman who processes palm sap water into palm sugar in Koreng Village, Tareran District, South Minahasa Regency. Palmt sugar is a sweetener for the manufacture of various kinds of food and beverage products. But the processing of palm sugar is only original palm sugar, so that at certain times the production results will have an impact on decreasing selling prices. Palm sugar processing can be made into various flavors such as ginger, curcuma, turmeric which will increase the added value, selling price and function of palm sugar. The purpose of the service is to develop processing of palm sugar sap into various flavors of ant sugar and to develop a marketing strategy with an attractive packaging design so that it can become a productive business. Diversification of palm sugar in various flavors as a basic ingredient for healthy drinks to increase endurance during this pandemic. The dedication method used is through presentations, demonstrations and practice of the process of making palm sugar with various flavors. As a result of this dedication, UKM Mekri and some palm sugar craftsmen in Koreng village can develop palm sugar through diversification of palm palm sugar with various variants of ginger, curcuma, turmeric flavors and increased knowledge about marketing strategies, attractive packaging designs that can increase the selling value of palm sugar products thereby increasing people's income